Factors associated to the failure of the root canal therapy - Toledo Reyes, Lilian (2018)
Objective: To identify the main factors associated to the failure of endodontic therapy. Methods: A relational prospective longitudinal study was performed in the city of Santa Clara in the period 2015-2017; resulting in a study group consisted of 448 patients. The selected variables associated with the failure of therapy were: age, gender, medical history, mouth opening, group location and position of tooth, root morphology, root apex number alteration root, visibility and size of the canals, branch, calcifications, pulp condition, reabsorption, diagnosis complexity, pain or swelling before therapy, difficulty radiographic diagnosis, cameral access complexity, pain during the treatment, quality of canal filling and periodontal disease. Results: Of 31 cases with reduced root canal size, 17 fail, being this the factor of greater significance (p<0.01) related to the therapy failure. Other factors with strong association were pulp condition (p=0.001), root morphology (p=0.005), as well as the quality of canal filling (p=0.009) which represent the 17%, 58% and 4.9% of the observed cases respectively. Conclusions: Age, group and location of tooth, root morphology, size of the canals, pulp condition, quality of filling and periodontal disease were the main factors associated to the root canal treatment failure.